Gambaran Kadar Profil Lipid dengan Derajat Keparahan pada Penderita Stroke Iskemik di Rumah Sakit Ibnu Sina Makassar Tahun 2021-2023 - Pratama, Marhumi Putri; Rachman, Mochammad Erwin; Wahyu, Sri; Muchsin, Achmad Harun; Eka, Andi Kartini (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study aims to describe the lipid profile levels and severity in ischemic stroke sufferers at Ibnu Sina Hospital Makassar in 2021-2023. The method used in this research is descriptive with a cross sectional study design. The results of this study found that the majority were female with 98 patients (58%) from the total population. The majority had high total cholesterol levels with 106 patients (63%) of the total population. The majority of triglyceride levels were normal with 159 patients (95%) of the total population. The majority of High Density Lipoprotein (HDL) levels were normal with 125 patients (74%) of the total population. The majority of Low Density Lipoprotein (LDL) levels were normal with 121 patients (72%) of the total population. Patients were measured using the National Institute of Health Stroke Scale (NIHSS), the majority of patients experienced moderate stroke with a total of 103 patients (61%) at Ibnu Sina Hospital Makassar during 2021-2023.